Use of Surfactant-BL in Adult Patients with Acute Respiratory Distress Syndrome - A. V. Vlasenko; D. A. Ostapchenko (Общая реаниматология)
The paper presents the results of a clinical trial of Surfactant-BL in adult patients with acute respiratory distress syndrome. Pulmonary biomechanics and gas exchange are shown to improve, the duration of respiratory support and the length of stay at an intensive care unit decrease, and the frequency of pyoseptic pulmonary complications reduces with early endotracheal administration of Surfactant-BL under artificial ventilation in acute respiratory distress syndrome.